Effect of Mirror Therapy Intervention on Motor Impairment Improvements in Elderly - Mar'ah, Novya Ashlahatul; Nurhayati, Nurhayati; Endah P., Tria Astika (STIKep PPNI Jawa Barat, 2023)
Aims: The slowness in the elderly activities is caused by a decrease in function of the musculoskeletal system, characterized by a decrease or increase in fat free mass which can cause a decrease in muscle mass, resulting in motor disorders. It is believed that providing range of motion exercises such as mirror therapy can stimulate the nerves in the motor cortex, thus providing signals to the brain to stimulate movement. Objective: This research is to identify the effect of mirror therapy on motor impairment in the elderly. Method: This type of research used quasi-experiment with two group pretest-posttest design approach and analysis method used Generalized Linear Model (GLM). The sample was 84 respondents, consisting of 42 intervention group samples and 42 control group samples. Sampling techniques were generally used as samples according to inclusion and exclusion criteria. The intervention was given for 4 weeks and assessed every week. Results: There was an effect of mirror therapy intervention on improving motor impairment in the elderly (p-value = 0.000). Conclusion: mirror therapy is a non-pharmacological therapy that can be used to improve motor impairment in the elderly.